Regional Government Authority in Determining Policies on the Master Plan of Tourism Development - Ni Luh Gede Astariyani; Ni Putu Wiwin Setyari; Bagus Hermanto (Kertha Patrika, 2020)
This study intends to examine the authority of local governments to regulate regional policies on tourism development master plan. This paper examines the legal issues related to the basis of the authority from philosophical, sociological, and juridical aspects of the formation of policies regarding tourism development plans. This paper focuses on the target, scope, content, and direction of Regional Regulations concerning tourism development plans to establish legislation and prioritizing aspects of the tourism industry, marketing destinations, and culture of Bali Tourism. It is a legal research that uses statutory, philosophical, theoretical, and conceptual approaches. The research resulted that the basis of authority for delegation of formation arrangements is regulated in the Law concerning Tourism, Government Regulation, and Regional Government Law related to the Master Plan of National Tourism Development. The basis of regional government authority in setting these policies is the enactment of local regulations of Bali Province, Badung Regency, Jembrana Regency, and Denpasar City concerning regional tourism development master plan. However, the mandatory obligations for regional government in determining tourism development master plan have not immediately been taken effect by the other regency governments in Bali Province.